Gastropods Community Structure in The Mangrove Ecosystem of The Sungai Rawa Village, Sungai Apit Sub-District, Siak District, Riau Province - Agustina, Endah; Adriman, Adriman; Fauzi, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTMangrove forests in the Sungai Rawa Village has been degraded due to anthropogenic activities. Decrement in mangrove ecosystem will negatively affects the aquatic organims in general, including the gastropods present in that area. To understand the community structure of gastropods in that mangrove ecosystem, a research was conducted on March 2018. There were 3 line transects and in each line there were 5 plots (1mx1m). The gastropods in the plots were collocted manually for 3 weeks. Result shown that there were 11 gastropods species present, they were Cassidula aurifelis, Cerithidea cingulata, Cerithidea obtusa, Chicoreus capucinus, Ellobium aurisjudae, Ellobium aurismidae, Littoraria melanostoma, Littoraria scabra, Nerita balteata, Neritina carnucopia and Telescopium telescopium. The gastropods density was ranged from 9 - 15 organisms/m2. The value of species richness index (Da) was 4.16 - 4.21, the diversity index (H’) was 2.99 - 3.13, the dominance index (C) was 0.12 - 0.14 and the uniformity index (E) was 0.90 - 0.93. The water quality parameters were as follows: temperature was 27 - 29ºC; pH was 7.3 - 7.7 and salinity was 26 - 27.3º/oo. Gastropods community structure in the mangrove ecosystem of the Sungai Rawa Village was good and there was no dominant species. Keywords: Diversity Index, Mollusca Community, Gastropods Population, Mangrove Forests